Pioglitazone Metformin Complex Improves Polycystic Ovary Syndrome Comorbid Psychological Distress via Inhibiting NLRP3 Inflammasome Activation: A Prospective Clinical Study - Qing-jun Guo; Jing Shan; Yi-feng Xu; Yan-yan Hu; Cui-lan Huo; Jing-yun Song; Chao-qun Wang; Hui Zhou; Chao-qin Yu; Qin Huang (Hindawi Limited, 2020)
Objective. This study aimed at investigating the therapeutic effect and mechanism of pioglitazone metformin complex preparation (PM) in polycystic ovary syndrome (PCOS) comorbid psychological distress. Methods. Seventy-five patients with PCOS comorbid psychological distress were randomly allocated into the PM, metformin, and placebo groups. The primary efficacy measure was the change from baseline to week 12 on the Symptom Checklist 90-R (SCL-90-R) scores. NLRP3 inflammasome, IL-1β, IL-6, TNF-α, and biochemical parameters were determined at baseline and at week 12. The participants were required to meet the criteria for PCOS (Rotterdam, NIH) and psychological distress (any factor scores of SCL−90−R>2). Results. The participants had significantly high scores on the SCL-90-R scales of anxiety and depression. PM significantly decreased anxiety and depression symptom severity (from 2.31±0.75 to 1.65±0.38, p<0.001, and from 2.08±0.74 to 1.61±0.46, p=0.010, at week 12, respectively). PM significantly decreased the expression of NRPL3 and caspase-1. Patients in the PM group experienced a significant reduction in IL-1β (from 98.42±14.38 to 71.76±13.66, p=0.02), IL-6 (from 87.51±8.74 to 71.98±15.87, p=0.02), and TNF-α (from 395.33±88.55 to 281.98±85.69, p=0.04). PM was superior to metformin in reducing total testosterone (2.24±0.74 versus 3.06±0.83, p=0.024, at week 12).Conclusions. This study is the first to reveal that PM alleviates psychological distress via inhibiting NLRP3 inflammasome and improves several markers, including total testosterone.